THE GUT–BRAIN AXIS IN AUTISM SPECTRUM DISORDER: MICROBIOTA, IMMUNE DYSREGULATION, AND THERAPEUTIC PERSPECTIVES - Alia Echtay Yarbou; Rami Mallah; Dominika Julia Kozdroń; Michalina Weronika Nieścioruk; Dominika Raether; Adam Andrzejewski; Paulina Szczepańska; Jacek Kowalski; Dominika Dutkiewicz; Adrian Mikołajuk (International Journal of Innovative Technologies in Social Science, 2026)
Background: Autism spectrum disorder (ASD) is a heterogeneous neurodevelopmental condition characterized by persistent difficulties in social communication, restricted and repetitive behaviors, and a high prevalence of co-occurring gastrointestinal, metabolic, and immune disturbances. Increasing evidence suggests that the gut–brain axis—a bidirectional communication network linking intestinal microbiota, immune signaling, metabolic pathways, and neural circuits—may play an important modulatory role in ASD-related neurodevelopmental processes. Scope: This review synthesizes current evidence on gut–brain axis physiology and examines how alterations in microbiota composition and function intersect with immune dysregulation, microbial metabolite signaling, and neurodevelopment in ASD. Findings from clinical studies, preclinical mechanistic research, and emerging microbiota-targeted therapeutic approaches are integrated to provide a systems-level perspective on microbiota–immune–brain interactions. Key Findings: Individuals with ASD frequently exhibit altered gut microbial diversity and composition, accompanied by functional disruptions in microbial metabolite pathways, including short-chain fatty acid and tryptophan metabolism. These changes are associated with impaired intestinal barrier integrity, systemic immune activation, neuroinflammatory signaling, and microglial dysfunction, processes that may contribute to excitatory–inhibitory imbalance and altered synaptic plasticity in the central nervous system. Microbiota-targeted interventions—such as probiotics, dietary modification, and fecal microbiota transplantation—demonstrate preliminary benefits for gastrointestinal symptoms and selected behavioral outcomes, although clinical evidence remains heterogeneous and limited. Conclusions: Current evidence supports a multifactorial model in which gut microbiota alterations act as modulatory amplifiers of neurodevelopmental vulnerability in ASD rather than as primary causal factors. Interactions among microbial metabolism, immune regulation, environmental exposures, and developmental timing appear central to this process. Future progress will depend on longitudinal, multi-omics approaches and biomarker-driven stratification to enable precision-based microbiota-targeted interventions.